In-game heart rate responses among professional baseball starting pitchers - Cornell, D. J.; Paxson, J. L.; Caplinger, R. A.; Seligman, J. R.; Davis, N. A.; Flees, R. J.; Ebersole, K. T. (The Journal of Strength and Conditioning Research, 2017)
The purpose of the current study was to characterize the in-game heart rate (HR) responses of baseball pitching. In-game HR was recorded from 16 professional baseball starting pitchers (mean ± SD, age = 22.1 ± 1.3 years; height = 187.9 ± 4.4 cm; weight = 90.5 ± 9.5 kg) for a total of 682 innings (home = 381, away = 301). All analyzed HR data were then normalized to each pitcher's age-predicted maximal HR (%HRmax). The group mean ± SD in-game %HRmax among all pitchers was 84.8 ± 3.9%, suggesting that baseball pitching is predominantly an anaerobic task. A split-plot mixed-model repeated measures analysis of variance identified a significant interaction effect between inning and game location (p = 0.042). Follow-up simple effects indicated that the in-game %HRmax was significantly different across innings, but only during home starts (p < 0.001). Specifically, pairwise analyses indicated that the in-game %HRmax during home starts were significantly (p = 0.05) higher in the first and second innings than in all other innings. In addition, follow-up simple effects indicated that the in-game %HRmax was significantly (p = 0.017) higher during home starts than away starts in the first inning (87.3 ± 3.6% vs. 85.8 vs. 3.8%, respectively). Thus, it is possible that inning-dependent psychological factors may have contributed to the observed changes in in-game physiological intensity across innings and that these factors are specific to game location. Consequently, strength and conditioning practitioners should prescribe high-intensity exercises when developing conditioning programs for professional baseball starting pitchers.